Gestão arquivística na era do cinema digital: formação de acervos de documentos digitais provindos da prática cinematográfica - Alessandro Ferreira Costa (2007)
The thesis had as its objective to investigate the possible relations between the fields of film studies and information science, specially archivology, disserting both on the historical and conceptual foundations that underpin the thinking and practice in these two fields separately, but on the points that become common when contextualized to the universe of Archives of Film. In addition, it includes a reflexion about the real conditions of the physical and virtual collections of filmic and non-filmic documents existent in institutions that guided the present study, namely: Arquivo Público Mineiro (APM), Arquivo Público da Cidade de Belo Horizonte (APCBH), Centro de Referência Audiovisual (CRAV), Escola de Belas Artes (EBA/UFMG) e Centro Universitário UNA. From this set of data, it was proposed to the document management methodology applied to the digital context that could guide the practice of audiovisual productions (film, tv and / or web) from the point of view of the organization and access to the whole series of documents produced and/or collected under the goal of a given project (film, series, journalism, website and the like) and consequent assessment and collection of mass documentary liable for purposes of research, culture and entertainment (secondary value of the document). For effective job of management, was established a plan for the classification of the document digital in the cinematograph context that determines not only the use of terms and codes common to those professionals involved with files audiovisual material, but also indicates model standard arrangement based on the structure of film production.